PKM Pemeriksaan Hemoglobin dan Penyuluhan Anemia Pada Remaja di Dusun Bencal, Desa Pandanwangi, Kecamatan Diwek, Kabupaten Jombang - Arifin, Zainul; Listihayu, Ariana; Lestari, Sri; Sayekti, Sri (Yayasan Daarul Huda Kruengmane, 2023)
Adolescent health is very important, because adolescents are a productive age group that will later develop into the nation's next generation. However, adolescents, especially female adolescents, have a ten times greater risk of health problems in the form of anemia than male adolescents. The integrated community service program for lecturers and students in PKKMD activities begins on December 18 to December 30, 2022, while anemia data collection for adolescents in Bencal Hamlet, Diwek District, Jombang Regency will be carried out on December 26, 2022. It is hoped that this will contribute to improving the health of village communities, especially related to the problem of anemia in adolescents. This program carries out health checks and counseling for village communities who come to the Bencal Hamlet, Pandanwangi Village, Diwek District, Jombang Regency. In the activity in collaboration with the Health Center and related apparatus, counseling was carried out regarding the introduction of the cyamethemoglobin method for detecting hemoglobin levels and various other information about anemia, especially for young women. In this activity, the results obtained from 11 adolescents who took part in the examination, 8 people had normal hemoglobin levels , and 3 low people. This activity also provides counseling about anemia to the people who attend. This can be used by related parties to make directives to the community in an effort to improve public health. There is also a need for an examination with more respondents and a wider coverage of the inspection area.